Cover Image, Volume 84, Issue 6. Issue 6 (June 2016) - Savino, Simone; Ferrandi, Erica Elisa; Forneris, Federico; Rovida, Stefano; Riva, Sergio; Monti, Daniela; Mattevi, Andrea
Abstract : The cover image, by Andrea Mattevi et al., is based on the Structure Note Structural and biochemical insights into 7β‐hydroxysteroid dehydrogenase stereoselectivity, DOI:10.1002/prot.25036 .